Comparison of Leak Detection Methods Used for Testing Large Area Membrane Roofs for Durability Assessment Purposes - Ksit, Barbara; Ratajczak, Maria; Żylińska, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents different types of commercially available roof waterproofing membrane systems used on roofs with large surface area. It deals with the causes of deterioration of such membranes due to environmental factors and describes the tests used to detect leaks and determination of the severity of deterioration of polymeric membranes taking into account the properties declared by their manufactures. The last part of the article is a case study comparing a brand new membrane with a membrane after 27 years in service.
Keywords: roof with large surface area; roofs of membrane; waterproofing systems; durability assessment; leak; dach o dużej powierzchni; dach membranowy; systemy hydroizolacyjne; ocena trwałości; nieszczelność